Actualization of Imam Al-Ghazali’s Maslahah Concept in the Context of Mixed Marriage - zarul arifin (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2023)
This abstract discusses the actualization of Imam Al-Ghazali's concept of maslahah within the context of mixed marriages. Imam Al-Ghazali, a prominent Islamic scholar, emphasized the importance of maslahah, which refers to the pursuit of societal welfare and the realization of benefits. Mixed marriages, involving individuals from different religious or cultural backgrounds, have become increasingly common in today's globalized world. However, such unions often present challenges, including cultural clashes, differing religious practices, and potential conflicts within families. In the context of mixed marriages, the concept of maslahah can play a significant role in promoting understanding, harmony, and social cohesion. It encourages individuals and communities to focus on the shared benefits and well-being derived from such unions. By prioritizing maslahah, couples can strive to find common ground, respect each other's beliefs, and foster an inclusive environment that embraces diversity. Imam Al-Ghazali's concept of maslahah emphasizes the importance of mutual consultation (shura) and the preservation of essential values and principles in society. Applied to mixed marriages, this concept encourages open dialogue, understanding, and compromise between partners and their respective families. It highlights the need to prioritize the well-being of individuals and society as a whole over individual desires or differences. The actualization of Imam Al-Ghazali's maslahah concept in the context of mixed marriages requires active engagement from religious scholars, community leaders, and families involved